PENERAPAN METODE 5R (RINGKAS, RAPI, RESIK, RAWAT, RAJIN) DAN IDENTIFIKASI POTENSI BAHAYA DI GUDANG BAHAN KIMIA LABORATORIUM MIPA - Riana Septiani; Mirandi Pratiwi (Industrika : Jurnal Ilmiah Teknik Industri, 2020)
This research is about Application of 5R methods ((Ringkas, Rapi, Resik, Rawat, Rajin) and indentification of hazard potential in Chemical Warehouse. And it aims to improve the work environment in the laboratory by using the 5R work method and identify potential hazards contained. Analysis of the two problems was carried out using several methods, namely for the implementation of warehouse layout with the 5R method, and for work safety using hazard identification & risk assessment using Pareto Chart Analysis to discuss the level of work accident risk from the highest to the lowest, and proceed by using a Fishbone Chart Analysis to analyze the types of work accidents from the factors that cause the risk of accidents. The index value before the application of 5R has a value of 20%, while the index value after improvement is 75.6% and the result of hazard identification has 23 hazard risks from 7 activities with an area that has a very high level of hazard risk. Keywords: 5R, occupational safety, hazard identification, risk assessment, work accidents, Chemical Warehouse